PENGGUNAAN MEDIA DAKON DALAM MENINGKATKAN KETERAMPILAN PEMBAGIAN BILANGAN BULAT - Muhammad Ilham Rosyadi (PUSAT PENELITIAN DAN PENGABDIAN MASYARAKAT (P3M) SEKOLAH TINGGI ILMU TARBIYAH AL-FATTAH SIMAN LAMONGAN, 2019)
This study aims to improve the learning outcomes of the material division of two-digit integers class 2 MI Miftahul Ulum Kebalankulon by using Media Dakon. The subjects in this study were students of class 2 MI Miftahul Ulum Kebalankulon, totaling 20 students, consisting of 14 students and 6 students. The object in this study is the arithmetic skills and the results of learning mathematics. Data collection methods used in this study were observation and tests with research instruments namely observation sheets and evaluation questions. The data analysis technique used in this research is descriptive qualitative and quantitative descriptive data analysis. The results showed that using the media can increase the math skills and learning outcomes of the material division of integers. In the quality of learning, after the implementation of the first cycle, the teacher's activities in teaching and student participation are in the good category. In the second cycle increased to very good. Improved learning outcomes are shown by increasing the average value of learning outcomes before being given an action that is 62.4 with completeness achieved by 10 students (50.0%), increased in the first cycle with an average test of learning outcomes of 68.7% with completeness achieved by 16 students (80%) in the good category. In the second cycle the average class increased to 82.5 with completeness achieved by 19 students (95%) and in the very good category.